Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fnins.2023.1203104
|View full text |Cite
|
Sign up to set email alerts
|

Generative AI for brain image computing and brain network computing: a review

Abstract: Recent years have witnessed a significant advancement in brain imaging techniques that offer a non-invasive approach to mapping the structure and function of the brain. Concurrently, generative artificial intelligence (AI) has experienced substantial growth, involving using existing data to create new content with a similar underlying pattern to real-world data. The integration of these two domains, generative AI in neuroimaging, presents a promising avenue for exploring various fields of brain imaging and bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 104 publications
1
9
0
Order By: Relevance
“…They can aid radiologists in the quantification and characterization of lesions, providing more accurate and reproducible measurements ( 133 ). Additionally, AI algorithms can help predict patient outcomes, such as the risk of recurrent strokes or response to treatment, based on imaging findings and clinical data ( 134 , 135 ). While, a study conducted by Voter AF and colleagues showed unexpectedly lower sensitivity and positive predictive values for Aidoc in diagnosing intracranial hemorrhage, which has raised concerns about the generalizability of these commercial AI tools ( 136 ).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…They can aid radiologists in the quantification and characterization of lesions, providing more accurate and reproducible measurements ( 133 ). Additionally, AI algorithms can help predict patient outcomes, such as the risk of recurrent strokes or response to treatment, based on imaging findings and clinical data ( 134 , 135 ). While, a study conducted by Voter AF and colleagues showed unexpectedly lower sensitivity and positive predictive values for Aidoc in diagnosing intracranial hemorrhage, which has raised concerns about the generalizability of these commercial AI tools ( 136 ).…”
Section: Future Directions and Conclusionmentioning
confidence: 99%
“…Generative AI for brain image computing and brain network computing: a review (Gong et al, 2023): This comprehensive review encapsulates the breadth of generative AI applications in brain imaging and network computing. It highlights how generative models facilitate the exploration of brain function and structure, aid in the early detection of neurological disorders, and contribute to the development of personalized treatment plans.…”
Section: Extensive Review On Generative Ai In Data Augmentationmentioning
confidence: 99%
“…In addition, B12 delays the onset of symptoms associated with dementia in older adults, and in adolescents it has been observed that borderline levels of this vitamin are associated with changes in cognitive functioning. In addition, some components of vitamin E are absorbed by the brain and are involved in the protection of the nerve membrane [73,74]. Additionally, we know that the intake of foods with low glycemic levels guarantees the maintenance of a low insulin index.…”
Section: Insights From Neuroimaging On Exercise and Nutrition's Impactmentioning
confidence: 99%